2017
DOI: 10.2480/agrmet.d-16-00012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of litter-bag and chamber methods for measuring CO<sub>2</sub> emissions from leaf litter decomposition in a temperate forest

Abstract: Leaf litter decomposition strongly affects the global carbon cycle through carbon dioxide CO 2 emissions to the atmosphere. The litter bag method LB and chamber method with litter addition and removal treatments C-LART have been used to quantify the litter decomposition rate and its resultant CO 2 flux. The C-LART method measures soil CO 2 fluxes in control, litter addition, and litter removal plots, and thereby decomposition rates are calculated from differences of the fluxes. However, no report has described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, the downside to the open-top chamber method was that it tends to be influenced by wind Table 1, Fang and Moncrieff, 1998;Liang et al, 2004 . The application of the closed dynamic chamber to measure R s was a relatively recent development compared with the other chamber methods Hall et al, 1990;Rochette et al, 1991; The popularisation of the compact IRGA had greatly influenced the applicability of the closed dynamic method and several types of dynamic chamber methods to measure R s Rochette et al, 1997 . In this method, only the air sample collected in the closed chamber is led into the CO 2 analyser with no ambient air flow into the chamber Rochette et al, 1997 . The measurement is conducted in a non-steady state under increasing CO 2 concentrations inside the chamber due to R s . There are several commercial portable-type closed dynamic chamber systems such as the Li6400 equipped with a soil respiration chamber 6000 -09, Li-cor, Lincoln, NE, USA , Li8100 Li-cor , or EGM-5 equipped with a soil respiration chamber SRC-2, PP-Systems, Amesbury, MA, USA ; many studies have used these systems Wang et al, 2005;Ohashi et al, 2008;Adachi et al, 2009;Liu et al, 2016a;Li et al, 2019b;Qin et al, 2019 . In recent research, the originally developed portable-type closed dynamic chamber systems have also been used in the field Takada et al, 2015;Sun et al, 2017;Gao et al, 2019;Zhao et al, 2021 .…”
Section: Dynamic Chamber Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the downside to the open-top chamber method was that it tends to be influenced by wind Table 1, Fang and Moncrieff, 1998;Liang et al, 2004 . The application of the closed dynamic chamber to measure R s was a relatively recent development compared with the other chamber methods Hall et al, 1990;Rochette et al, 1991; The popularisation of the compact IRGA had greatly influenced the applicability of the closed dynamic method and several types of dynamic chamber methods to measure R s Rochette et al, 1997 . In this method, only the air sample collected in the closed chamber is led into the CO 2 analyser with no ambient air flow into the chamber Rochette et al, 1997 . The measurement is conducted in a non-steady state under increasing CO 2 concentrations inside the chamber due to R s . There are several commercial portable-type closed dynamic chamber systems such as the Li6400 equipped with a soil respiration chamber 6000 -09, Li-cor, Lincoln, NE, USA , Li8100 Li-cor , or EGM-5 equipped with a soil respiration chamber SRC-2, PP-Systems, Amesbury, MA, USA ; many studies have used these systems Wang et al, 2005;Ohashi et al, 2008;Adachi et al, 2009;Liu et al, 2016a;Li et al, 2019b;Qin et al, 2019 . In recent research, the originally developed portable-type closed dynamic chamber systems have also been used in the field Takada et al, 2015;Sun et al, 2017;Gao et al, 2019;Zhao et al, 2021 .…”
Section: Dynamic Chamber Methodsmentioning
confidence: 99%
“…Typical Q 10 values of R s are roughly in the range of 2.0 -3.0, based on previous observational studies that have largely taken place in relatively humid Asian regions covering sub-tropical forests, and temperate forests Tan et al, 2013;Noh et al, 2017;Sun et al, 2017;Teramoto et al, 2017 . In the meta-analysis presented in Wang et al 2010 , worldwide observations mainly from forests showed that the arithmetic mean of the Q 10 value was 2.67, despite a large variation in the Q 10 values from 0.98 to 6.27. These observed Q 10 values tend to be higher compared to global estimates of Q 10 .…”
Section: Temperature and Moisture Responses Of R Smentioning
confidence: 97%
“…Soil CO2 flux was measured on each collar using a previously described method (Cui et al 2021;Sun et al 2017) between 10:00 and 16:00 at intervals of approximately three weeks from August 2019 through November 2020 with a five-month suspension from mid-November 2019 through mid-April 2020. Seedlings were carefully pulled from the collars before flux measurements, although they were rarely found.…”
Section: Soil Co2 Fluxmentioning
confidence: 99%
“…Before the treatments, CO2 efflux was also measured in September and October 2014 to check for initial spatial variations among the CC, SC, LC, and TC collars. The measurements were conducted manually on each collar between 10:00 and 16:00 using a closed chamber system with two 50 cm tall cubic chambers made of transparent acrylic plastic (Sun et al 2017). CO2 concentration and air temperature inside the chamber were measured every 5 s with an infrared gas analyzer (LI820; Li-Cor Inc., Lincoln, NB, USA) and a thermocouple probe (MHP; Omega Engineering, Stamford, CA, USA).…”
Section: Soil Co2 Effluxmentioning
confidence: 99%